Synthesis, Structure, and Reactivity of Acid‐Free Neutral Oxoborane. Issue 35 (24th June 2021) - Wang, Hanqiang; Zhang, Jie; Yang, Jingting; Xie, Zuowei
Abstract: An efficient synthesis of an acid‐free neutral oxoborane of the type carboranyl‐B(carbene)=O has been developed via a serendipitous discovery from the reaction of 1, 2‐[BBr(carbene)]‐o‐carborane with AgOTf. This represents a new type of oxoborane. The stabilization of this oxoborane may be attributed to 1) kinetic stabilization provided by a bulky 3D carboranyl ligand and 2) thermodynamic stabilization offered by a carbene ligand. Crystallographic analyses support the presence of the shortest terminal B=O double bond ever reported thus far. Its reactivity has also been examined. Abstract : A new type of acid‐free neutral oxoborane has been prepared via a serendipitous discovery, from the reaction of 1, 2‐[BBr(carbene)]‐ o ‐carborane with AgOTf in which the shortest B=O distance observed so far has been measured, as confirmed by single‐crystal X‐ray analyses.